Evaluation of Platelet Activity Markers in Prognostic Value of Children with Crimean-Congo Hemorrhagic Fever - Güven, Ahmet Sami; Duksal, Fatma; Metin Akcan, Özge; Aygüneş, Utku; Oflaz, Mehmet Burhan (Journal of Pediatric Infectious Diseases, 2020)
Objective The aim of this study is to investigate the prognostic value of platelet (PLT) activity markers in children with Crimean-Congo hemorrhagic fever (CCHF) and compare results with healthy controls.Materials and Methods A total of 135 patients with CCHF and 100 healthy children were included in this retrospective study. Mean age was 12.4 ± 3.3 years in CCHF group, and 92 patients were male. We measured PLT count, mean platelet volume (MPV), platelet distribution width (PDW), and mean platelet mass (MPM) as PLT activity markers.Results A statistically significant decrease in MPM and PLT, and significantly higher levels of PDW and activated partial thromboplastin time (aPTT) and no significant difference in MPV were observed in patients with CCHF compared with controls. Although there were no significant differences between the severe and nonsevere CCHF groups in term of MPV and PDW, the MPM value was significantly decreased in severe patients (p < 0.001). Furthermore, MPM values were inversely correlated with aPTT (r = −0.617, p = 0.015), and positively correlated with PLT (r = 0.703, p < 0.001) which are considered likely to be indicators of disease severity. Multivariate logistic regression analysis revealed MPM as an independent risk factor for severe disease.Conclusion Our study demonstrated that MPM values were decreased in severe cases compared with nonsevere in children with CCHF. The MPM as an indicator of PLT activation at the time of diagnosis in children with CCHF can be used as a prognostic index for disease severity.
Keywords: Crimean-Congo hemorrhagic fever; mean platelet mass; platelet activity markers; disease severity; children